Analisis Pengaruh Tingkat Profitabilitas Terhadap Nilai Pasar Saham Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2011-2013 - Utomo, Fanny Evelyna; , Imron Rosyadi, S.E., M.Si (2015)
This research purposed to analyze the influence of changes in the profitability which include the changes in Net Profit Margin (NPM), Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) to changes in stock price on companies listed in Indonesia Stock Exchange (IDX) in 2011-2013. This research data used secondary data that getting from financial report of companies listed in Indonesia Stock Exchange (IDX). The research result indicated that F test (simultaneous), the changes of NPM, ROA, ROE, and EPS significantly influence the stock price changes. According to the t test (partially), the variable of ROE and EPS changes, significantly influence the stock price changes and variable of NPM, and ROA changes, does not significantly influence the stock price changes. Changes in stock price are influenced by changes in NPM, ROA, ROE, and EPS by 71,6% and the rest is influenced by other factor.